Implementación de una matriz de selección técnica de equipos y herramientas en operaciones de subsuelo para las fases de completamiento, workover y abandono en los pozos de un campo de la cuenca del Valle Medio del Magdalena (2020)
This degree work describes the process of building a technical selection matrix of tools and equipment for subsurface operations, which allows to handle large volumes of information, and to access it efficiently. This was built using Excel’s Visual Basic for Applications tool. The operation consists of entering data and certain specifications, then processing the information, and as a result, obtaining the equipment and tools that best fit the parameters entered.